Penerapan Metode Design Thinking Pada Perancangan User Interface Aplikasi Rifqitenda Untuk Meningkatkan Kemudahan Dalam Fitur Persewaan Wedding Decoration - Nurudin, Anwar; Widyanto, R Arri; Sasongko, Dimas (Journal of Information System Research (JOSH), 2024)
In the current digital era, an efficient and integrated system is a very important need, especially in the service sector such as tent rental. RifqiTenda is a company that provides rental services for various equipment for celebrations such as tents, chairs, tables and decorations. However, the rental process is still often hampered by problems such as lack of information transparency and limited accessibility. The aim of this research is to build a tent rental system to achieve the rental process and improve user experience. The method used in this research is the Design Thinking Method which is used as a framework to guide the design process, which includes four main stages: empathy, definition, ideation, prototype and test. The results of this research are a web-based application for tent rental by implementing the design think method. Based on the test results on the Rifqi Tenda application prototype, using the usability testing labyrinth, a score of 81 and System Usability Scale (SUS) was obtained, and the SUS score was 78.5, which is in a good ranking. This indicates that most users find this application easy to use. It is hoped that the results of the research will have an influence in improving the user experience in the tent rental process at Rifqitenda.